Clinical Observations with Evoked Otoacoustic Emissions at Mayo Clinic - Robinette, Martin S. (Journal of the American Academy of Audiology, 2003)
Clinical applications of transient evoked otoacoustic emission (TEOAE) measures began in 1989 at Mayo Clinic Rochester. Normative data indicates: a) greater TEOAE level for women and right ears beginning in the teen years, b) mean TEOAE levels remain relatively stable through the first seven decades of life, c) between subject EOAE level variability for normal hearing adults is high (up to about 30 dB) while within subject variability is low (about 4 dB), suggesting EOAEs should not be used to estimate pure-tone thresholds but are valuable in monitoring hearing status. Good frequency specificity of TEOAEs is demonstrated across high frequency hearing loss. Examples of TEOAEs in differential diagnosis are provided for cases of sudden hearing loss, auditory neuropathy and eighth nerve tumors including pre and post operative testing assessing changes in auditory function related to surgical procedures. Finally, our experience with TEOAEs in newborn hearing screening is described.
Keywords: Otoacoustic emissions; transient otoacoustic emissions; auditory neuropathy; sudden hearing loss; gender